Telemedicine and Rural Healthcare: Bridging Gaps in Access, Equity, and Infrastructure - Fissabrina, Lulu Qalbina (Indonesian Scientific Publication, 2024)
Telemedicine is increasingly vital in reducing healthcare disparities in rural and underserved areas by lowering travel burdens, reducing costs, and improving diagnostic efficiency. Literature was collected from PubMed, Scopus, and Google Scholar, focusing on rural healthcare contexts. Evidence from China, India, Australia, and Latin America shows that telemedicine enhances healthcare access and patient outcomes, particularly during the COVID-19 pandemic. Telemedicine also promotes equity by reaching marginalized groups, though challenges remain, including inadequate internet connectivity, limited device availability, digital illiteracy, and cultural skepticism. Policy support, infrastructural investment, and context-specific innovations are essential for sustainable implementation. This review concludes that telemedicine represents a transformative strategy to strengthen rural healthcare systems and advance access, equity, and sustainability globally.